Conceptual Directions in Slovenian Rural Geography - Drozg, Vladimir; Pelc, Stanko (Journal for Geography, 2008)
The paper shows an overview through teoretical and conceptional directions in Slovene rural geography. In the firts part of the article, the changes in understanding of the term rural area are shown, in the second some theoretical concepts are disscoused. The last chapter brings an overview of the most often researched topics in the field of rural geography in Slovenia.